Identification of Quantitative Trait Loci for Phytic Acid Concentration in Maize Grain Under Two Nitrogen Conditions - Jian-chao LIU; Ya-qun HUANG; Wen-qi MA; Jin-feng ZHOU; Fen-ru BIAN; Fan-jun CHEN; Guo-hua MI (Journal of Integrative Agriculture)
Phytic acid (PA) is the main storage form of phosphorus (P) in seeds. It can form insoluble complexes with microelements, thereby reducing their bioavailability for animals. Identification of quantitative trait loci (QTLs) associated with grain PA concentration (PAC) is essential to improve this trait without affecting other aspects of grain nutrition such as protein content. Using a recombinant inbred line (RIL) population, we mapped QTL for grain PAC, as well as grain nitrogen concentration (NC) and P concentration (PC) in maize under two N conditions in 2 yr. We detected six QTLs for PAC. The QTL for PAC on chromosome 4 (phi072-umc1276) was identified under both low-N and high-N treatments, and explained 13.2 and 15.4% of the phenotypic variance, respectively. We identified three QTLs for grain NC, none of which were in the same region as the QTLs for PAC. We identified two QTLs for PC in the low-N treatment, one of which (umc1710-umc2197) was in the same interval as the QTL for PAC under high-N conditions. These results suggested that grain PAC can be improved without affecting grain NC and inorganic PC.